Andrastone A From the Deep-Sea-Derived Fungus Penicillium allii-sativi Acts as an Inducer of Caspase and RXRα-Dependent Apoptosis - Xie, Chun-Lan; Xia, Jin-Mei; Lin, Ting; Lin, Ying-Jie; Lin, Yu-Kun; Xia, Man-Li; Chen, Hai-Feng; Luo, Zhu-Hua; Shao, Zong-Ze; Yang, Xian-Wen (Frontiers in Chemistry, 2019)
Two new (1, 2) and one known (3) meroterpenoids were isolated from the deep-sea-derived fungus Penicillium allii-sativi. The relative structures of new compounds were determined on the basis of extensive analysis of the NMR and MS data. And the absolute configurations were established by ECD calculations. Andrastone A (1) was a rare andrastin bearing an unusual cyclopentan-1,3-dione. It showed selectively antiproliferative effect against HepG2 tumor cells with an IC50 value of 7.8 μM. Mechanism study showed that apoptosis via Caspase and RXRα pathways were responsible for the inhibitory effect.